Analysis of appropriate overtaking position under equal block lengths - O. Sangphong; S. Siridhara; V. Ratanavaraha (International Association of Lowland Technology, 2019)
This paper studies train passing operation and determine line capacity by checking minimum headway. The analysis is based on the blocking time model displayed on the time space diagram where minimum headway and minimum waiting time are calculated. The study found that the capacity is affected by the number of blocks and the overtaking block position. The graph between the overtaking position and capacity is symmetrical, in which capacity is reducing when the overtaking position is far from the center of the line. The overtaking position that maximizes capacity is not affected by speed nor block length. In the case of even number of blocks, the appropriate location to overtake is (n / 2) +1 while in case of odd number of blocks, the overtake position is at (n+1)/2 and (n+3)/2. Both positions maximize the line capacity for each case. In addition, when the block length was reduced the capacity increased and decrease dwell time.